Synthesis and Sedative-Hypnotic Activity of Novel N-[3-(3-Aminomethylpyrazolo[1,5-a]pyrimidin-7-yl)phenyl]-N-ethylacetamide Derivatives - Wang, Yu-Jun; Song, Chang-Wei; Li, Xia; Li, Ying; Yin*, Shu-Fan (Asian Journal of Chemistry, 2013)
N-[3-(3-Aminomethylpyrazolo[1,5-a]pyrimidin-7-yl)phenyl]-N-ethylacetamide derivatives were synthesized and evaluated for sedative-hypnotic activity in vivo. These derivatives contain sulfa, amine and amide three series. The structures of these newly prepared compounds were confirmed by melting point, IR, 1H NMR spectroscopy and HRMS. The sedative-hypnotic activity of the synthesized compounds was evaluated by testing their effects on the locomotor activity of mice. Compounds 3h, 4d and 5c were found to have more smoothly and lastingly activity and these products can be recognized as lead compounds for further optimization. The structure-activity relationship (SAR) showed that derivatives containing electron-withdrawing group or conjugation structure on C7 position were the most effective compounds. These findings not only preliminary screened few good target compounds, but also provided useful structural information for rational design and synthesis.